Anisotropic Growth of Al‐Intercalated Vanadate by Tuning Surface Hydrophilicity for High‐Rate Zn‐Ion Storage. Issue 1 (13th September 2020) - Wu, Hao; Ming, Fangwang; Lei, Yongjiu; Zhang, Wenli; Alshareef, Husam N.
Abstract : Aqueous zinc‐ion battery (ZIB) cathodes with high rate performance are still lacking due to the sluggish kinetics of Zn 2+ insertion. Herein, preferential 2D spreading surface is constructed on conductive carbon paper (C‐paper) supports by disclosing hierarchical porous structures. The unique surface hydrophilicity enables anisotropic growth of layered Al‐intercalated vanadate nanobelts with high‐aspect ratios. As a cathode of ZIB, the preintercalated vanadate nanobelts with a large interlayer spacing (1.38 nm) exhibit high specific capacities and excellent rate performance (534 and 221 mA h g −1 at 1 and 20 A g −1, respectively). Moreover, chemically resistant HfO2 layers are applied by atomic layer deposition to prevent effectively the cathode from degradation, leading to an outstanding cycling stability (88% retention at 1000 cycle). The anisotropic growth of 2D electrode materials by tuning the surface hydrophilicity provides an effective pathway for designing improved electrode materials for various energy storage technologies. Abstract : Unique surface hydrophilicity is induced via fabricating hierarchical architecture on C‐paper, which enables anisotropic growth of 2D layered Al‐intercalated vanadate nanobelts with high‐aspect ratios and a large interlayer spacing. This cathode material with HfO2 passivation layer shows high specific capacities, outstanding rate performance, and cycling capability for zinc‐ion battery.